Introduction to cytogenetics 3 - SenGupta, Sioban (Henry Stewart Talks, 2010)
Robertsonian translocations, 21:21 fission, Reciprocal translocation, 2:2 segregation, 3:1 segregation, Pericentric inversion, Paracentric inversion, Diagnosis of chromosome abnormalities, Screening, Prenatal diagnosis, CVS, Amniocentesis, Molecular cytogenetics, Ambiguous results, The future